Chapter The Link between Universities and the Labour Market: Perceiving the Building of Employability Processes in Higher Education - Boffo, Vanna (Studies on Adult Learning and Education, 2023)
The topic that we will deal with in this essay is central for the development of higher education in Italy, Europe and the world. Universities as academic and educational institutions have changed radically over the last 50 years. At present, their task is to educate and train new brackets of the population for a future in which competencies and learning will be the points of reference for an ever more rapidly and intensely evolving and developing world. To this end, it becomes important to reflect on the topic of building university curricula in the educational sector and on the competencies achieved by the graduates from master's courses designed to train the professional figure of pedagogist. The aim of the article is to concentrate on the internal aspects of university programmes whose goal is to train true professionals in the world of education and training, who are able to take on the responsibilities required of them and to display the necessary competencies. Here, it will be offered the last results of a qualitative research on the perceptions of the learning outcomes of two groups of master degree students in Adult Education and Pedagogical Sciences at the University of Florence. The principal points will consist into the reaching of the employability competences and into the acquiring of the knowledges about the labour market.